Detecting alliance ruptures: the effects of the therapist’s experience, attachment, empathy and countertransference management skills - Corinne Talbot; Rose Ostiguy-Pion; Esther Painchaud; Claudelle Lafrance; Jean Descôteaux (Research in Psychotherapy, 2019)
Accurate alliance rupture detection is a prerequisite to any successful repair process. Despite its importance, however, rupture detection remains a struggle for most therapists. Supporting the existence of a therapist effect on therapy outcomes, rupture detection skills may rely on certain therapists’ personal characteristics. The aim of this study was to verify whether alliance rupture detection performance is related to therapists’ personal characteristics. One hundred and eight undergraduates, trainees and mental health professionals participated in an experimental task assessing their alliance rupture detection ability. Participants also completed attachment, empathy and countertransference management self-reported measures. Participants with clinical experience (trainees and professionals) reported more alliance ruptures, accurate or not, than those with no clinical experience (undergraduates). Trainees reported more accurate ruptures and less inaccurate ones than the two other groups. Attachment anxiety was positively associated with accurate ruptures detection for undergraduates, while this association proved negative for trainees and therapists. Perspective-taking, a cognitive dimension of empathy, was negatively associated with accurate rupture detection, whereas personal distress, an affective dimension of empathy, was negatively associated with accurate ruptures detection for trainees, and positively associated for undergraduates. Self-insight, a component of countertransference management, revealed a negative association with accurate rupture detection for trainees. These findings suggest that therapists vary as to their rupture detection ability and that this ability is related to certain personal characteristics. They also highlight the importance of specific training and clinical supervision for both trainees and experienced therapists in order to improve their detection ability.